The great escape - Phillips, Susan Elizabeth (New York William Morrow, 2012)
Lucy Jorik, the daughter of the former president of the U.S., jilts her soon-to-be husband at the altar and embarks on the adventure she has been waiting for
Sequel to: Call me irresistible
1
NEW, LITERATURE
Keywords: Humorous fiction; Life change events -- Fiction; Man-woman relationships -- Fiction; Motorcyclists -- Fiction; Self-realization -- Fiction; Love stories; Road fiction